Das unzufriedene Volk: Protest und Ressentiment in Ostdeutschland von der friedlichen Revolution bis heute - Pollack, Detlef (transcript, 2020)
In public discourse, East Germans like to portray themselves as victims of German unity. Yet, they have proved to be powerful political actors from the peaceful revolution to the present day. In the revolutionary upheaval of 1989, the political dynamic did not originate from the small group of civil rights activists, but from the population itself. And today, the East German population dominates public debates through its voting behaviour and through its victim discourse. Through the East German protest behaviour we can see how a population constitutes itself as a nation under the conditions of a dictatorship and how, in democracy, collective self-empowerment degenerates into resentment.